Didactical Views of S. Šalkauskis - Karčiauskienė, Stasė (Acta Paedagogica Vilnensia, 1991)
The article presents didactic ideas of Stasys Šalkauskis. Understanding didactics as a science of intellectual education, involving the activity of teacher and students in which the teacher is a middleman between a taught subject and the student, Šalkauskis pays considerable attention to the analysis of the characteristics of the participants of the training process. Šalkauskis concentrates mostly on theoretical problems of didactics, analyzes them concisely but deeply, consistently, clearly defining the content and substance of pedagogical terms. Especially Šalkauskis was interested in learning the process as a whole. He discusses the logical, psychological and pedagogical aspects of the process and their interaction. The paper also analyzes the narrower didactic aspects, such as the learning environment, teaching objectives, teaching content, teaching methods and forms. Šalkauskis didactic reasoning shows the effort to combine classical pedagogy with of the new educational theory of the end of 19th and beginning of 20th century.